Why dragonfly? What's up with the moon? [videorecording (DVD)]. (Why Dragonfly?, 2005)
When a couple of kids wonder what's wrong the the moon, a magical dragonfly whisks them away to the Space Science Institute and the Denver Museum of Nature and Science to find the answer.